The presidents' war : six American presidents and the Civil War that divided them - DeRose, Chris (Christopher) (Guilford, Connecticut : Lyons Press, an imprint of Globe Pequot Press, 2014)
Tells the story of how five ex-presidents--for and against Abraham Lincoln (but mostly against)--maneuvered, seceded, plotted, advised and aided during the Civil War while Lincoln navigated the minefield they created.
Prologue: in Jackson's time -- I met nullification at its threshold -- The freshmen -- The setting sun -- ... and Tyler, too -- War in Mexico! -- The 30th Congress -- A final settlement -- A hell of a storm -- The final election of the old America -- General Jackson is dead! -- The first and only choice of the Republicans of Illinois -- A startling tide of reckless fanaticism -- Five against Lincoln -- The gathering storm -- The tug has to come -- The last winter of peace -- That all will yet be well -- Home again -- Breakfast at Fort Sumter -- The meeting that never was -- The border states -- Twilight at Wheatland, dawn at Manassas -- To lose Kentucky is nearly the same as to lose the whole game -- Capture on the high seas -- The bottom is out of the tub -- Greenbacks and ironclads -- Any explanations which you may offer would be acceptable -- West and east -- The very vortex of hell -- Destroy the rebel army, if possible -- A continuation of war by other means -- A storm of lead -- If my name ever goes into history, it will be for this act -- We are ruined -- The brave men, living and dead -- The Fourth of July -- A new birth of freedom -- Our old home -- Those not skinning can hold a leg -- Not unworthy to remain in my present position -- The last full measure -- Epilogue: do not despair of the republic.
Includes bibliographical references (pages 363-366) and index.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Adversaries; Lincoln, Abraham, -- (1809-1865); Lincoln, Abraham, -- 1809-1865.; United States -- Politics and government -- 1861-1865.; Ex-presidents -- Political activity -- United States -- History -- 19th century; United States -- Politics and government -- 1815-1861.; Politique et gouvernement; Politique et gouvernement -- 1815-1861.; United States -- History; Enemies; Politics and government; United States; 1800-1899; History